The retail brand personality—Behavioral outcomes framework: Applications to identity and social identity theories - Kuo, Ya-Hui (Frontiers in Psychology, 2022)
This study applies identity and social identity theories to develop and test a framework in which retail brand personality influences consumer outcomes [i.e., positive word-of-mouth (WOM) about and patronage intention toward the retailer] through public and/or private self-congruity, strengthened by shopping conspicuousness situation, and retail brand identification (RBI). This is the first study to include social shopping situations to study brand personality and self-congruity. A questionnaire with a 2 (retailer image format) × 2 (shopping situation conspicuousness) between-subjects design was conducted on a sample of US consumers. Structural equation modeling was used to test the hypotheses. The findings suggest a framework in which Genuine, the most influential dimension of retail brand personality, predicted outcome behaviors both directly and indirectly through self-congruities and RBI. The high shopping conspicuousness situation strengthened the relationship between public self-congruity and the overall RBI. The concept of RBI provides an additional theoretical perspective for guiding future research on shopper–brand relationships. In addition, this framework provides practical implications for retail environment design and customer-brand relationship management.